Structural and dielectric performance of the Ba(Zn1/3Nb2/3-xSbx)O3 perovskite ceramics - Qasrawi, A F.; Sahin, Ethem İlhan; Emek, Mehriban; Kartal, Mesut; Kargin, Serdar (IOP Publishing, 2019)
In this work, we have explored the antimony doping effects on the structural and dielectric properties of Ba(Zn1/3Nb2/3)O3 ceramics (BZN). The ceramics displayed perovskite structures with a lattice constant that decreases with increasing Sb content. The antimony solubility limit of the BZN ceramics is Below this limit and in the range of the microstrain, the dislocation density and the stacking faults decreased and the crystallite size increases with increasing Sb content in the composition of BZN. When the limit is exceeded minor phases are predicted by software analysis and confirmed by the experimental techniques. The presence of these phases is also verified by the scanning electron microscopy and energy dispersive x-ray spectroscopy techniques. Increasing the Sb content is observed to decrease the value of the dielectric constant. The Sb doped BZN ceramics exhibits high dielectric quality factors that nominate it for applications in electronics as radio waves resonators.
Keywords: x-ray diffraction; Ba(Zn1/3Nb2/3)O-3 ceramics; Sb doping; dielectric